MODEL PENGEMBANGAN USAHA KECIL DAN MENENGAH (UKM) DENGAN PENDEKATAN KLUSTER - Mawardi, Mukhammad Kholid (IQTISHODUNA, 2009)
The increasing of contribution of small and medium enterprises (SMEs) toward Indonesia economy stimulates government to provide more attention in promoting SMEs. Numereous studies show that business clustering have been succed in fostering SMEs, therefore many governments including Indonesia tend to benchmark cluster policy. However, the Indonesian SMEâ€™s characteristics should be taken into account in formulating cluster policy. This paper aims toÂ  propose a cluster model in promoting SMEs in Indonesia, based on literature review of business clustering across the globe.